2019
DOI: 10.1016/j.jmmm.2019.03.046
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and mechanical effects of Mn substitutions in AlFe2B2

Abstract: The mechanical and magnetic properties of the newly discovered MAB-phase class of materials based upon AlFe 2 B 2 were investigated. The samples were synthesised from stoichiometric amounts of all constituent elements. X-ray diffraction shows that the main phase is orthorhombic with an elongated b-axis, similar to AlFe 2 B 2 . The low hardness and visual inspection of the samples after deformation indicate that these compounds are deformed via a delamination process. When substituting iron in AlFe 2 B 2 with m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…The fact that neither the B‐FAB herein nor the dense samples studied in Ref. [8,10,11] were treated in HCl and show better high‐temperature stability supports this conjecture.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The fact that neither the B‐FAB herein nor the dense samples studied in Ref. [8,10,11] were treated in HCl and show better high‐temperature stability supports this conjecture.…”
Section: Resultsmentioning
confidence: 97%
“…The thermal stability of bulk Mn 2 AlB 2 , 7,8 MoAlB, 9 and Fe 2 AlB 2 8,10,11 borides has been reported in argon (Ar), nitrogen (N 2 ), or vacuum atmospheres. Kota et al showed that bulk Mn 2 AlB 2 was stable up to ≈1380 K and decomposes into the binary boride MnB and Al‐rich phases above this temperature 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of Cr 2 AlB 2 , CrB 2 and Al grains is also confirmed by the EDS maps in Figure 5b and their orientation relationship can be determined from the electron diffraction patterns. Thus, the Cr 2 AlB 2 (200), the CrB 2 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and the Al (−220) reflections marked in Figure 7b-d coincide. These correspond to aligned lattices with spacings of 1.4315, 1.4860 and 1.4686 Å in the ideal structures, respectively.…”
Section: Resultsmentioning
confidence: 85%
“…This phase has been suggested as a potential material for magnetic refrigeration due to its magnetocaloric properties [10]. In contrast, Mn 2 AlB 2 is antiferromagnetic, while solid-solutions mixing Mn and Fe on the metal sites give a disordered ferrimagnetic phase [11]. In the Cr-Al-B system, three phases in the series (CrB 2 ) n CrAl with n = 1, 2, 3 have been synthesised [8].…”
Section: Methodsmentioning
confidence: 99%